ANALISA HIDROLOGI PERMUKAAN DALAM HUBUNGANNYA DENGAN DEBIT BANJIR DAS LUKULO HULU DENGAN MENGGUNAKAN DATA PENGINDERAAN JAUH - Raharjo, Puguh D; Winduhutomo, Sueno; Widayanto, Kristiawan; Puswanto, Eko (Universitas Negeri Semarang, 2016)
Lukulo upstream watershed represents a watershed in Karangsambung Geological Nature Preserve, thisbasin is located administratively in Central Java Province with Area is Â± 281,394 km2. In rainy season theriver discharge of upstream lukulo steep increase, while in the dry season is very small. The purpose of thisstudy was to analyze the surface hydrology in relation to the flood discharge in the Lukulo upstreamwatershed using remote sensing data. Data of SRTM image was processed DEM hydro-processing in theform of flow determination and network catchment extraction produced 16 units of sub-drainage. Results ofcoeffitient runoff value estimates using Bransby and Williams method is 58% with flood discharge wasestimated using the rational method at 562, 098 m3/second which had difference with the actual flooddischarge at 1, 662 m3. Value of flood discharge in the Lukulo upstream watershed is relatively large andcan cause flooding /overflowing of rivers in the surrounding area.